Change in Risk Status During Labor in a Large Norwegian Obstetric Department: A Prospective Study. Issue 1 (March 2015) - Lippert, T.; Nesje, E.; Koss, K.S.; Oian, P.
Abstract : ( Acta Obstet Gynecol Scand. 2013;92(6):671–678)